Business Strategy of Construction Commercial One Member Limited Liability Bank stage 2017 – 2022 = Chiến lược kinh doanh của ngân hàng thương mại TNHH MTV Xây dựng Việt Nam giai đoạn 2018-2022. Luận văn ThS. Kinh doanh: 60 34 01 - Nguyễn, Minh Công, d1989- (2019)
CHAPTER 1: LITERATURE REVIEW. CHAPTER 2: OVERVIEW OF CBBANK. CHAPTER 3 : THE BASIS FOR NEW BUSINESS STRATEGIES FORMULATION OF CBBANK . CHAPTER 4: PROPOSING NEW LONG TERM STRATEGIES FOR CBBANK.